Pre-clinical and preliminary dose-finding and safety studies to identify candidate antivenoms for treatment of envenoming by saw-scaled or carpet vipers (Echis ocellatus) in northern Nigeria. - Abubakar, S; Abubakar, I; Habib, A; Nasidi, A; Durfa, N; Yusuf, P; Larnyang, S; Garnvwa, J; Sokomba, E; Salako, L; Laing, G; Theakston, R; et al. (2010)
The aim of this study was to identify candidate antivenoms with specific activity against the venom of the saw-scaled or carpet viper (Echis ocellatus) in northern Nigeria, where bites by this species cause great morbidity and mortality but where effective antivenoms have become scarce and unaffordable. Selected antivenoms were destined to be compared by randomised controlled clinical trials (RCTs). Standard pre-clinical neutralisation assays were carried out in rodents. We included two licensed antivenoms of established clinical efficacy and 6 candidate antivenoms. Although 6 of the tested antivenoms showed promising efficacy, all but 3 were excluded from further study because of inadequate pre-clinical efficacy or because they were unavailable or unaffordable for the anticipated RCTs. Median effective doses (ED(50)) of the remaining three candidate antivenoms suggested that the following doses might neutralise the maximum observed venom yield of 24.8 mg (dry weight) of venom milked from captive E. ocellatus: 10 ml of MicroPharm "EchiTAb G" (ET-G) antivenom; 30 ml of Instituto Clodomiro Picado "EchiTAb-Plus-ICP" (ET-Plus) antivenom; 50 ml of VacSera, Cairo "EgyVac" antivenom. A preliminary clinical dose-finding and safety study of these three antivenoms was carried out in 24 patients with incoagulable blood after E. ocellatus bites who were not severely envenomed. A 3+3 dose escalation design was employed. Initial doses of 10 ml ET-G and 30 ml ET-Plus restored blood coagulability in groups of 6 patients with early mild reactions (pruritus only) in not more than one third of them. EgyVac antivenom did not fulfil efficacy or safety criteria in 12 patients. On the basis of these results, ET-G and ET-Plus were selected for comparison in a RCT.